Digitalization and Financial Inclusion as an MSMe Business Sustainability Strategy: A Case Study In The Food and Beverage Sector - Ika Fitriyani; Muhammad Nur Fietroh; Novi Kadewi Sumbawati; Ismawati; Afina Aurellya Kamal; Yuliana (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the role of digitalization and financial inclusion of Micro, Small, and Medium Enterprises (MSMEs) as business sustainability strategies. Digital transformation and inclusive financial access are important factors in increasing the competitiveness of MSMEs in the digital economy era. This research uses a qualitative approach with a case study method on MSMEs in the food and beverage sector. Data collection was carried out through in-depth interviews, observations, and documentation, while data analysis used thematic analysis techniques. The results show that digitalization contributes to improving operational efficiency, expanding market access through digital platforms, and strengthening relationships with customers. On the other hand, financial inclusion facilitates access to formal financial services, such as financing and digital payment systems, thereby supporting more professional business management. The synergy between digitalization and financial inclusion has proven to be able to increase the innovation capacity and productivity of MSMEs, which ultimately encourages business transformation towards a higher scale. However, there are several obstacles faced, such as low digital and financial literacy and limited access to infrastructure. Therefore, support from various parties is needed through training, mentoring, and policies that support the empowerment of MSMEs in a sustainable manner